Family therapy with ethnic minorities - Ho, Man Keung (SAGE sourcebooks for the human services)
Janice Matthews Rasheed (Loyola U., Chicago) and Mikal Rasheed (Northeastern Illinois U.) provide a revised edition of the 1987 text by the late Dr. Man Keung Ho, written for advanced students and practitioners working in clinical practice with American racial and ethnic minority families. The new edition updates the various demographics, and incor